Influence of complex organic mixes on the basis of polioles on receptor’s the device of white rats in subakut experiment - Sirenko, E.; Kycherenko, E. (Actual Problems of Medicine and Pharmacy, 2021)
Ability of organic mixes on the basis of polioles is established to cause different changes of parameters receptor’s linkages and systems of mediaeven regulation of an endocellular metabolism. Decrease in affinity to ligands, reduction of quantity of places receptor’s linkages and increase of number glucocortikoid receptors in a fabric of a brain and a liver of rats is registered.